TECHNOLOGY OF THE COMPOUND PRODUCTION - D. M. Kukuj; Ju. I. Lednev; I. B. Odarchenko (Литьë и металлургия)
It is shown that using of compound KBM allowed to reduce the expense of binder, to increase the solidity of mixture and its plastic properties. Besides, the complex of additives included into KBM increased the antiburning-on properties and resistance to scab-forming of agglutinant sand.